Synthesis and Antimicrobial Activity of 6,7,8,9-Tetrahydro-5(H)-5- nitrophenylthiazolo[2,3-b]-quinazoline-3(2H)-one Derivatives - Praveen Kumar, P.; Rajendra Prasad, Y.; Kumar, N.R.; Sridhar, S. (Asian Journal of Chemistry, 2010)
6,7,8,9-Tetrahydro-5(H)-5-nitrophenylthiazolo[2,3-b]- quinazolin-3-(2H)-one (2) has been synthesized as intermediate from 3,4,5,6,7,8-hexahydro-4-nitro phenyl quinazolin-2-thione (1) with chloro acetic acid. The treatment of intermediate with various aldehyde afforded respective benzylidine derivatives (3a-c). This on further treatment with phenyl hydrazine yielded hydrazine derivatives (4a-c). The structures of the compounds were supported by spectral data. The synthesized compounds have been screened for antimicrobial activity.